(untitled) (American Journal of Business Management, Economics and Banking, 2023)
This article discusses the trends observed in the implementation of deposit policy by commercial banks and issues related to their impact on deposit policy. In the article, the deposit policy is a key part of the overall banking policy, which defines the strategy and tactics of commercial banks to conduct deposit activities. It also contains the author’s suggestions and recommendations on the problems of deposit policy and their solutions